HIGH- RESOLUTION MELTING (HRM) CURVE ANALYSIS: NEW APPROACH USED TO DETECT BLAD AND DUMPS IN URUGUAYAN HOLSTEIN BREED - Federici, María Teresa Teresa; Branda Sica, Andrea; Artigas, Rody; Briano, Carolina; Dutra, Fernando; Llambí, Silvia (Archives of Veterinary Science, 2018)
The widespread use of artificial insemination has allowed the expansion of genetic progress. However, it also brought consequences such as the expansion of lethal hereditary diseases and the increase in inbreeding. The object of this study was to establish a fast and sensitive molecular assay to detect bovine leukocyte adhesion deficiency (BLAD) and deficiency of uridine monophosphate synthase (DUMPS) carriers in Uruguayan Holstein cattle by means of high resolution melting (HRM) curve analysis. By testing previously confirmed carrier and non-carrier animals, we set up a rapid, simple, and inexpensive diagnostic test using PCR followed by HRM curve analysis. The PCR-HRM genotyping method was effective for the discrimination of BLAD and DUMPS homozygous genotypes, and the BLAD heterozygous genotype. We conclude that the PCR-HRM assay is a robust, reliable, and economical tool for the detection of these mutations in the Holstein breed, which may be implemented in genetic selection programs.